Macroeconomic Policy Frameworks for Resource-Rich Developing Countries : Background Paper 1. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper provides deeper insights on a few themes with regard to the experience with macroeconomic management in resource-rich developing countries (RRDCs). First, some stylized facts on the performance of these economies relative to their non-resource peers are provided. Second, the experience of Fund engagement in these economies with respect to surveillance, programs, and technical assistance is assessed. Third, the experience of selected countries with good practices in the management of the natural resource wealth is presented. Fourth, the experience of IMF advice in helping RRDCs set up resource funds is discussed. Finally, the main themes and messages from the IMF staff consultation with external stakeholders (CSOs, policy makers, academics) are presented.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet